Minimizing Asymmetric Information in Online Markets through Knowledge Management - Arbi, Khalil Ahmed; Kausar, Abdul Rashid; Salim, Imran (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
This article is about the role of knowledge management in minimizing the asymmetric information in online business. The asymmetry of information is the prime concern in online markets where consumer and seller are located in distant locations and they cannot see each other. The success of ecommerce business depends heavily on the minimization of asymmetric information between the seller and buyers. As the online business is done through codified knowledge and it is easy to manage the codified knowledge so by efficient use of KM principles and processes it has now become easy to minimize the asymmetric information among the seller and buyers. The article discusses the types of asymmetric information which can ne be minimized through use of codified online knowledge.